Removal of P-chloro Phenol from Aqueous Solutions Using Chestnut Shell Modified by Sulfuric Acid: Study of Adsorption Kinetic and Isotherm - Hatam Godini; Fatemeh Taheri; Bahram Kamarehie; Parvin Mostafaei; Seddigheh Saeedi (Muhandisī-i Bihdāsht-i Muḥīṭ, 2015)
Background: Present of p-chloro phenol in the environment due to high toxicity, mutagenic and carcinogenic effects, powerful odor production and stability in the environment caused to be categorized as priority pollutants. The aim of this study was to investigate the removal of p-chloro phenol from aqueous solution using chestnut shell modified by sulfuric acid.